2011
DOI: 10.5194/hess-15-1577-2011
|View full text |Cite
|
Sign up to set email alerts
|

The green, blue and grey water footprint of crops and derived crop products

Abstract: Abstract. This study quantifies the green, blue and grey water footprint of global crop production in a spatially-explicit way for the period 1996-2005. The assessment improves upon earlier research by taking a high-resolution approach, estimating the water footprint of 126 crops at a 5 by 5 arc minute grid. We have used a grid-based dynamic water balance model to calculate crop water use over time, with a time step of one day. The model takes into account the daily soil water balance and climatic conditions f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

56
1,644
44
54

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,884 publications
(1,798 citation statements)
references
References 39 publications
56
1,644
44
54
Order By: Relevance
“…Fischer (2011) analyzed livestock feed energy balances and found that in 2000 about 55% to 60% of available grassland biomass globally was required for animal feeding. Mekonnen and Hoekstra (2010) highlighted the water footprint of livestock production on a global scale. A further concern is the sector's contribution to climate change and pollution.…”
Section: Climate Change and Livestock -A Literature Reviewmentioning
confidence: 99%
“…Fischer (2011) analyzed livestock feed energy balances and found that in 2000 about 55% to 60% of available grassland biomass globally was required for animal feeding. Mekonnen and Hoekstra (2010) highlighted the water footprint of livestock production on a global scale. A further concern is the sector's contribution to climate change and pollution.…”
Section: Climate Change and Livestock -A Literature Reviewmentioning
confidence: 99%
“…In the meantime however, the average water footprint of almond cultivation is 8047 m 3 /ton, approximately twice as much as cotton, and twenty three to forty times more than the other main arable commodities -strawberries (347 m 3 /ton), tomatoes (214 m 3 /ton) and lettuce (237 m 3 /ton) (Mekonnen & Hoekstra 2010). Annually, California has approximately 53 billion m 3 of water available (combining surface water that is diverted and groundwater pumped to the surface).…”
Section: Disturbances and Resilience In Food Systems: Drought In Calimentioning
confidence: 99%
“…Results of a modelling study using the CROPWAT model indicate that the use of water for low value crops is a major concern in the Guadiana basin and that future water management policy should emphasize "more cash and nature per drop" (Aldaya and Llamas, 2009, p. 2). A global water footprint study by Mekonnen and Hoekstra (2011), also using CROPWAT, suggests that crop water footprints are influenced by agricultural management practices rather than climate and that this presents an opportunity for improved water productivity. Different footprint analyses for the same area can exhibit great variability as a result of the many assumptions and uncertainties introduced to the model, especially regarding crop properties.…”
Section: Uses Of Hydrological Modelsmentioning
confidence: 99%